Beyond Capital Relocation: Comparative Constitutional Study from Kazakhstan for the Future of Indonesia’s Nusantara - Alendra Nauval Mufti Rayhan (Punggawa Law Review, 2026)
The relocation of Indonesia’s capital city to Nusantara (IKN) represents the culmination of a long-standing discourse on capital relocation dating back to the era of President Sukarno. Although intended to address Jakarta’s structural challenges and promote equitable national development, the implementation of IKN continues to face various constitutional and governance issues, including legal uncertainty, limited public participation, questions regarding the legitimacy of the Nusantara Capital Authority, agrarian conflicts, and the absence of local democratic representation. This study aims to analyze the constitutional problems surrounding the relocation of Indonesia’s capital city and to compare them with the successful relocation of Kazakhstan’s capital from Almaty to Astana. The research employs a normative juridical method using statutory and comparative approaches. The findings reveal that Kazakhstan’s success was supported by strong legal certainty, policy consistency, sustainable development planning, protection of citizens’ rights, and the preservation of representative local institutions within the capital’s governance structure. In contrast, Indonesia continues to encounter normative and institutional obstacles that may hinder the effectiveness of the relocation process. This study concludes that strengthening legal certainty, ensuring meaningful public participation, protecting community rights, and enhancing democratic representation are essential mechanisms for achieving an effective, efficient, and sustainable capital relocation.